The Application of Iddhipãda IV for Successful Organization Administration - Kositathammo, Phra Kosit (Journal of Thammawat, 2022)
The application of Iddhipãda IV for successful organization management that the administrators of the organization should behave according to Iddhipãda IV, namely 1) Chanda: which is satisfied with that love, the administrators must always love their works in order to have the mind to concentrate on their works to be successful. The administrators must do good, correct, honest, fair things and work hard to achieve success, 2) Viriya: which is work hard that thing, the administrators must be diligent, work with effort, strength, patience, discouragement, determine to do good deeds, perseverance and seek for knowledge in order to manage the work that they are responsible for better, 3) Citta: which is concentration that thing, the administrators must pay attention to their works, concentrate on the mind without letting the mind distract, enthusiastic by working with energy, work carefully, wisely, reasonably that is appropriate to prevent the mistakenness in the organization administration, and 4) Vimamsã: which is persistence in considering the reasons that thing, the administrators are diligent, consider, contemplate, examine, finding reasons and always checking for shortcoming, planning for ways to improve work, applying wisdom to ponder what is wrong, correct by adhering the principles of morality and ethics in their own profession ethics that should not be tainted.